Reaction to Endoplasmic Reticulum Stress via ATF6 in Amyotrophic Lateral Sclerosis Deteriorates With Aging - Prell, Tino; Stubendorff, Beatrice; Le, Thanh Tu; Gaur, Nayana; Tadić, Vedrana; Rödiger, Annekathrin; Witte, Otto W.; Grosskreutz, Julian (Frontiers in Aging Neuroscience, 2019)
Amyotrophic lateral sclerosis (ALS) is a multisystemic neurodegenerative disorder. Given that peripheral blood mononuclear cells (PBMCs) serve as a “window to the central nervous system” we aimed to answer whether endoplasmic reticulum (ER) stress in ALS-PBMCs is related to disease aggressiveness. We studied ER stress in the PBMCs of 49 patients with ALS and 31 age- and sex-matched healthy controls. The expression of a main ER stress marker, activating transcription factor 6 (ATF6), was significantly higher in ALS compared to controls, but did not correlate with age, disease severity, disease duration and disease progression rate. When ATF6 expression levels were plotted against relative D50 (rD50)-derived disease phases derived from the D50 ALS model, two distinct clusters of patients were observed: cluster 1, with progressively increasing ATF6 expression levels and cluster 2, which demonstrated stable ATF6 expression over the disease course. Individuals in the two clusters did not significantly differ in terms of ALS Functional Rating Scale-Revised (ALSFRS-R), disease aggressiveness, disease duration and subtype. However, patients with the increasing ATF6 level were significantly younger, indicating that aging processes might be related to ER stress in ALS. Our data suggest that the reaction to ER stress during disease course may be compromised in older patients with ALS.